PERANCANGAN DAN PEMBUATAN SISTEM PENGAMBILAN SAMPAH SECARA OTOMATIS MENGGUNAKAN PLC OMRON CP1E-E40DR-A - Putri, Windi Darmaisha; Sjahrul, Yurika (Jurnal TEDC; Vol 19 No 1 (2025): JURNAL TEDC, 2025)
The increasing volume of waste in urban areas necessitates a more efficient waste management system. Conventional manual collection methods are often ineffective and costly, facing issues such as schedule delays and dependency on labor. This study proposes an automated waste collection system using the OMRON CP1E-E40DR-A PLC, integrating waste detection sensors and robotic mechanisms. The effectiveness of sensor distance was tested 10 times to determine the optimal range that does not cause delays in the conveyor. Of the tests, 5 showed no delays, with an average efficient sensor distance of 50%. The total time efficiency for collecting 10 grams of waste was measured over 5 trials, with 3 tests demonstrating efficient distribution times. The average efficient time for the distribution process reached approximately 54.55%. The findings of this research highlight the potential of automated systems in enhancing waste management efficiency in urban areas.